Part of Cumberland Peninsula, Baffin Island - American Geographical Society of New York (1929)
"Map presented to Parker D. Cramer by Corporal Maginnis of Canadian Royal Mounted Police, July 26, 1929, at Port Burwell."; "Acquired by gift Sep. 27, 1929 from Mr. Parker D. Cramer."; Indexed in: Manuscript and annotated maps in the American Geographical Society Library: a cartobibliography Grayscale; 1:1,300,000